A ação penal nos crimes contra a liberdade sexual: estudo sobre a (in)visibilidade das mulheres no processamento jurídico-penal da violência sexual - Silva, Luiza Ferreira (2021)
The present work aims to investigate how the trajectory of the criminal action in crimes against sexual freedom – and the debates of the legal actors involved in this process – means an (in)visibility of the women victim of sexual violence, considering that female victimization is quite expressive in this type of conduct, one of the ways in which gender violence manifests itself. Through the monographic procedure, the present research, of an exploratory nature, is based on inductive reasoning, as it starts from bibliographical and empirical studies, in addition to documentary and statistical data about sexual victimization, in order to arrive at a general answer about how women are seen in the legal-criminal treatment of the processing of crimes against sexual freedom. At first, the research assumes a predominantly descriptive bias, contextualizing the specificities surrounding sexual victimization, through the approach of three concrete cases of great media and social relevance, and addressing the legislative path taken by the legal-penal processing of sexual violence in Brazil. It was realized that it went from a status quo of privatization of the sexual criminal conflict to its absolute publicity, a path that reveals the development of a discourse of intense use of criminal law as a way to mitigate sexual violence and to ensure protection of victims. In a second step, the research takes an explicative bias, on which the theoretical bases of work are explained, related to victimology and critical and feminist criminologies. This theories helps to understand how the legal-criminal processing traditionally excludes the victim from the agency of her conflit and may represent a harmful scenario for her, especially when she is a sexual violence survivor. In this case, the revitimization is even more perceived, based on patriarcal domination. Therefore, a third moment arrives, in which it is explained how this legal trajectory of the legal-penal processing of sexual violence, immersed in the hostile and sexist reality of the criminal justice system, represents a public invisibility of women, who only appear in the discursive scope of a fallacious and precarious protection, represented by the Criminal Law. This protection, which, in the current form of unconditional public criminal action, disregards factors and difficulties inherent to sexual violence linked to the victims and contributes to the maintenance of a political demotion status for women and for female issues such as gender violence. The work also discuss some ways that are considered possible for a legal-criminal processing of sexual violence more aligned with the specificities of sexual victimization. It was concluded, in this sense, that the legislative path of criminal action in crimes against sexual freedom reflects the perennial invisibility of women who are the target of sexual violence, whether when understanding their suffered experience as a mere private matter of family honor, or when, at present, shows the criminal justice system as the only and mandatory solution. This ends up annihilating the victim's participation and reinforcing the same stereotypes that are at the base of gender domination.